Biocompatibility of new cement based capping material prepared from eggshell and biopolymer (chitosan). - Hemn M. Sarmamy; Dara H. Saeed (Erbil Dental Journal)
Background and Objective: This study aimed to evaluate the biocompatibility of a newly prepared cement-based capping material made from eggshell and biopolymer (chitosan) with Mineral Trioxide Aggrigate MTA and Biodentine. Methods: Fifteen male rabbits aged about 4-7 months of comparable weight more than 2.0 kg were selected. Animals were handled and maintained in accordance with international recommendations. The animals were divided into 3 groups, five rabbits for each group, for three time intervals (7, 14, and 21 days).Four specimens (4 mm long and 1 mm inner diameter) were inserted for each animal according to the following groups; Group 1: Empty pockets (control), Group 2: The Experimental material with a powder/liquid ratio of1 scoop: 8 drops by using glass slab with aid of cement metal spatula, Group 3: Mineral trioxide aggregate MTA which was mixed according to manufacturing instructions and Group 4: Biodentine which was mixed according to manufacturing instructions. Results: The histological preparation in control group at 7 days time period demonstrated simple inflammatory reaction represented by slight looseness of the collagen fibers with increase the extracellular spaces between the fibers indicating mild edematous inflammation. For the Experimental group, MTA and Biodentine group there was great similarity in the tissue reaction when comparedwith control group. At 14 days time period, the edematous inflammatory reaction appeared to be reduced and the collagen fibers arranged closer to each other when compared with the previous time period this was the same for other the groups.At 21 days time period For control, Experimental, MTA and Biodentine group there were complete resolution of the edematous reaction with the formation of thick collagen bundles accompanied by typical fibroblast cells. Conclusions: The implantation of the experimental material in the subcutaneous tissue of the rabbit’s back demonstrated very limited inflammatory reaction that didn’t differ from MTA and Biodentine group in all time intervals.